Analisis Kontribusi, Efektivitas dan Kenaikan Target Pajak Restoran Terhadap Pendapatan Asli Daerah Provinsi DKI Jakarta Tahun 2015 – 2019 - Sindy Meidiana Dwi Jayanti; Maulana Malik Muhammad (UNIVERSITAS KALBIS, 2022)
In restaurant tax revenue, there are several components that need to be known how the contribution, effectiveness and increase in the restaurant tax target to the regional original income of DKI Jakarta Province. The purpose of this study was to determine the criteria for contribution, effectiveness, and increase in the presentation of restaurant tax targets as a source of PAD for DKI Jakarta Province in 2015 – 2019. The data analysis method used was descriptive qualitative analysis using secondary data. The results of this study indicate that the restaurant tax contribution is included in the